Posterior urethral valve with unilateral vesicoureteral reflux and patent urachus: A rare combination of urinary tract anomaliess - Atobatele, Mutiu O. (Urol Ann, 2015)
Posterior urethral valve (PUV) is a common cause of lower urinary tract obstruction in male infants with an incidence of 1:5000-8000. PUV continues to be a significant cause of morbidity and ongoing renal damage in infants and children. It can coexist with vesicoureteral reflux (VUR) in about 50% of cases and also with patent urachus in about one-third of cases. It is a case of a 22-day-old full-term male child who presented with poor urinary stream and progressive abdominal distension of 5-day duration as well as leakage of clear fluid from umbilicus of 1-day duration. Abdominopelvic ultrasonography showed bilateral hydronephrosis. Micturating cystourethrogram also showed features of bladder outlet obstruction and PUV. In addition, a grade V left VUR and a fistulous tract between the dome of the urinary bladder and the umbilicus, which was consistent with a patent urachus was demonstrated. In conclusion, this case demonstrates a rare combination of congenital urinary tract anomalies involving PUV, left VUR and patent urachus.